(untitled) (Academicia Globe: Inderscience Research, 2022)
The article presents data on the treatment of infertility against the background of extragenital endometriosis. On the basis of the gynecological department of the 1st clinic of the Samarkand State Medical University, a comparative analysis of the conservative and surgical treatment of endometriosis was carried out, as a result of which the patients were divided into 2 groups. As a result of studies, natural fertility was restored in 44% of patients.